Family preference for the presence of cortical yellow (Baghdad Science Journal, 2006)
The population density of the insect on Alorat and fruits located in the lower part of the tree more than the middle part of the plant and insect in one place and demonstrates that there is a nest there were conducted laboratory and field studies on citrus Hsasahanwaa and the Alvdaúaa distribution of cortical insect yellow ....